DESIGN SPECIAL TOOLS FOR HANDLING AND LIFTING CNC HAAS V-F1 - Yudi Siswanto; Hendi Lilih Wijayanto; Inelwan Inelwan (BRILIANT: Jurnal Riset dan Konseptual, 2026)
The relocation of the Haas V-F1 CNC machine in a vocational education environment requires a special lifting tool that is safe, precise, and suitable for the limitations of campus facilities. This study aims to design and validate a special lifting tool that is compatible with the characteristics of the 3,539 kg Haas V-F1 CNC machine at the Morowali Metal Industry Polytechnic. The research method used an engineering design approach that included collecting technical data on the machine, structural static calculations, CAD modeling, and strength validation through finite element analysis (FEA). The analysis results show that at a nominal load of 34,682 N, the lifting tool has a maximum Von Mises stress of 1.49 × 10⁸ N/m², a maximum deflection of 3.63 mm, and a safety factor (FoS) of 2.4, which indicates safe operating conditions and is well below the yield strength of structural steel. Gradual loading tests show that the structure still works elastically up to an additional load of 500 kg with a FoS of 1.3, but reaches a critical condition at an additional load of 650 kg with a FoS approaching 1.0. Thus, the lifting device is recommended to operate at a nominal load with a maximum additional load of 250 kg. This research resulted in a safe, practical, and feasible lifting device design that can be used as an operational standard for lifting CNC machines in vocational education environments.